Energy consumption, efficiency, and greenhouse gas emissions study of petroleum coke and coal chemical looping combustion for power generation systems - Yingying XIA; Lingchen LIU; Mengxiang ZHU; Huiju CAO; Dong XIANG (Meitan xuebao)
Poor-quality petroleum coke is often used as fuel because of its high carbon content and calorific value, but its combustion process will emit a lot of CO2. Using the petroleum coke chemical looping combustion (CLC) for power generation is an effective way to realize its clean utilization, but the process still faces the problem of low conversion rate of petroleum coke. Mixing petroleum coke with coal as fuel can significantly improve the reactivity of petroleum coke. Therefore, this study established a CLC power generation system with a mixture fuel of petroleum coke and coal at a mass ratio of 1:1 and coal as the only fuel. The amount of oxygen carrier circulation required for a full reaction of decomposed fuel in the fuel reactor and the air flow required for the regeneration of oxygen carrier in the air reactor were optimized. The novel system was compared with a petroleum coke CLC power generation system in terms of system efficiency, life cycle fossil energy consumption and greenhouse gas emissions. The results show that the optimum mass ratios of circulating oxygen carrier to fuel required in the petroleum coke-coal and coal CLC power generation systems are 26.43 and 24.19, while their optimum mass ratios of air to fuel required for regenerating oxygen carrier are 9.22 and 8.43. The energy efficiencies of the new CLC power plant are 36.77%, which are 8.96 and 2.20 percentage points higher than that of the CLC power plant using petroleum coke and coal as fuel alone. The life cycle fossil energy consumption and the greenhouse gas emissions of the petroleum-coal hybrid CLC power plant are 9.52 GJ/MWh and 302.76 kg CO2 eq/MWh, which are 2.56 and 0.27 GJ/MWh, 35.27 and 4.03 kg CO2 eq/MWh lower than that of petroleum coke and coal power plants alone. The energy efficiency of the power generation system can be significantly increased by mixing petroleum coke with coal to improve the combustion conversion rate of petroleum coke, while the life cycle fossil energy consumption and greenhouse gas emissions of the power generation system can be reduced.